Efficacy and safety of cilostazol-nimodipine combined therapy on delayed cerebral ischaemia after aneurysmal subarachnoid haemorrhage: a prospective, randomised, double-blinded, placebo-controlled trial protocol - Chad F Claus; Doris Tong; Diana Sigler; Matthew Bahoura; Prashant Kelkar; Boyd Richards; Teck M Soo; Troy Dawley; Sina Rajamand; Lucas Garmo (BMJ Open)
Introduction Delayed cerebral ischaemia (DCI) due to cerebral vasospasm (cVS) remains the foremost contributor to morbidity and mortality following aneurysmal subarachnoid haemorrhage (aSAH). Past efforts in preventing and treating DCI have failed to make any significant progress. To date, our most effective treatment involves the use of nimodipine, a calcium channel blocker. Recent studies have suggested that cilostazol, a platelet aggregation inhibitor, may prevent cVS. Thus far, no study has evaluated the effect of cilostazol plus nimodipine on the rate of DCI following aSAH.Methods and analysis This is a multicentre, double-blinded, randomised, placebo-controlled superiority trial investigating the effect of cilostazol on DCI. Data concerning rates of DCI, symptomatic and radiographic vasospasm, length of intensive care unit stay, and long-term functional and quality-of-life (QoL) outcomes will be recorded. All data will be collected with the aim of demonstrating that the use of cilostazol plus nimodipine will safely decrease the incidence of DCI, and decrease the rates of both radiographic and symptomatic vasospasm with subsequent improvement in long-term functional and QoL outcomes when compared with nimodipine alone.Ethics and dissemination Ethical approval was obtained from all participating hospitals by the Ascension Providence Hospital Institutional Review Board. The results of this study will be submitted for publication in peer-reviewed journals.Trial registration number NCT04148105